Visually and memory guided saccades in a case of cerebellar saccadic dysmetria. Issue 9 (September 1994) - Kanayama, R; Bronstein, A M; Shallo-Hoffmann, J; Rudge, P; Husain, M
Abstract : Saccades under four specific test conditions (visually guided, visually remembered, vestibular remembered, and cervical remembered) were studied in a 38 year old man with ocular dysmetria due to an angioma of the dorsal cerebellar vermis. The aim of the study was to investigate if the saccadic disorder was specific to certain subsets of saccades elicited by different sensory modalities. The experiments showed that initial saccades were equally hypermetric in all four conditions and that final eye position was normal in all memory guided saccade tests. Eye movements differed after the initial saccade, however. Whereas corrective saccades were seen in most visually guided and visually remembered experiments, postsaccadic centripetal drifts were documented in non-visual (vestibular and cervical) remembered saccades. These results indicate that the cerebellar vermis modulates the amplitude of the initial saccade (pulse size of saccadic innervation) independently of the saccadic task. The finding that post-saccadic drift never occurred when saccades were programmed using visual positional information suggests that the dorsal vermis may participate in the process of pulse step integration of saccades elicited by memorised vestibulo-cervical information.